2007
DOI: 10.1038/sj.leu.2404735
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide and proteasome inhibitor bortezomib synergistically induce apoptosis in leukemic cells: the role of protein kinase Cδ

Abstract: Arsenic trioxide (ATO) and proteasome inhibitor bortezomib have been successfully applied to treat acute promyelocytic leukemia (APL) and multiple myeloma (MM), respectively. Their synergistic effects with other anticancer drugs have been widely studied. Here, we investigated the potential synergy of bortezomib and ATO on Bcr-Abl þ leukemic K562 cells. The results showed that cotreatment of bortezomib at 32 nM, a half concentration for growth arrest, and ATO at 1 lM, a dose with no significant cytotoxic effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…There is published evidence that BCR-ABL expression is associated with increased proteasome activity; primitive CML cells express higher levels of BCR-ABL than their more mature counterparts and BCR-ABL ϩ cell lines are susceptible to PI. 18,22,39,40 We have extended this work to demonstrate that CD34-enriched samples taken at diagnosis from patients with CP CML undergo apoptosis in SFMϮ5GF with bortezomib exposure. This effect was replicated in 7 different patient samples and the drug was consistent in its effect.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There is published evidence that BCR-ABL expression is associated with increased proteasome activity; primitive CML cells express higher levels of BCR-ABL than their more mature counterparts and BCR-ABL ϩ cell lines are susceptible to PI. 18,22,39,40 We have extended this work to demonstrate that CD34-enriched samples taken at diagnosis from patients with CP CML undergo apoptosis in SFMϮ5GF with bortezomib exposure. This effect was replicated in 7 different patient samples and the drug was consistent in its effect.…”
Section: Discussionmentioning
confidence: 96%
“…These studies used BCR-ABL ϩ cell lines both sensitive and resistant to IM and demonstrated antiproliferative and apoptotic effects. [39][40][41] In addition, the PI Z-Ile-Glu(OtBu)-Ala-Leucinal selectively inhibits colony formation by CD34 ϩ BCR-ABL ϩ progenitor cells. 41 Despite promising in vitro effects, there are little in vivo data.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them use Btz in combination with other drugs (Yu et al, 2003;Dai et al, 2004;Dasmahapatra et al, 2006;Yan et al, 2007) or lack the use of control cells (Gatto et al, 2003). In our case, we have used Btz alone at a dose that has no effect on BaF/3 cells that do not express Bcr-Abl1, showing that Btz alone is sufficient to arrest the cell cycle and induce apoptosis specifically in Bcr-Abl1-expressing cells.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of PKC in AML cells induces cell death through the downregulation of heterogeneous nuclear ribonucleoprotein K [380], phosphorylation of eIF2 [381] and -actin [382], and activation of MAPKs (JNK and p38) [383] and caspase-3 [384,385]. In addition, when wogonin, a natural monoflavonoid, is added to AML U937 cells, cell differentiation and G 1 phase arrest are induced through PKC -mediated upregulation of p21 proteins [386].…”
Section: And Amlmentioning
confidence: 99%